Influence of Abutment Design on Stiffness, Strength, and Failure of Implant‐Supported Monolithic Resin Nano Ceramic (RNC) Crowns. (14th March 2014) - Joda, Tim; Huber, Samuel; Bürki, Alexander; Zysset, Philippe; Brägger, Urs
Abstract: Background: Recent technical development allows the digital manufacturing of monolithic reconstructions with high‐performance materials. For implant‐supported crowns, the fixation requires an abutment design onto which the reconstruction can be bonded. Purpose: The aim of this laboratory investigation was to analyze stiffness, strength, and failure modes of implant‐supported, computer‐assisted design and computer‐aided manufacturing (CAD/CAM)‐generated resin nano ceramic (RNC) crowns bonded to three different titanium abutments. Materials and Methods: Eighteen monolithic RNC crowns were produced and loaded in a universal testing machine under quasi‐static condition according to DIN ISO 14801. With regard to the type of titanium abutment, three groups were defined: (1) prefabricated cementable standard; (2) CAD/CAM‐constructed individualized; and (3) novel prefabricated bonding base. Stiffness and strength were measured and analyzed statistically with Wilcoxon rank sum test. Sections of the specimens were examined microscopically. Results: Stiffness demonstrated high stability for all specimens loaded in the physiological loading range with means and standard deviations of 1, 579 ± 120 N/mm (group A), 1, 733 ± 89 N/mm (group B), and 1, 704 ± 162 N/mm (group C). Mean strength of the novel prefabricated bonding base (group C) was 17% lower than of the two other groups. Plastic deformations were detectable for all implant‐abutment crown connections. Conclusions: Monolithic implant crowns made of RNC seem to represent a feasible and stable prosthetic construction under laboratory testing conditions with strength higher than the average occlusal force, independent of the different abutment designs used in this investigation.